NOTCH1 Pathway is Involved in Polyhexamethylene Guanidine-Induced Humidifier Disinfectant Lung Injuries - Lee, Eun (Yonsei Med J, 2020)
An outbreak of fatal humidifier disinfectant lung injuries (HDLI) occurred in Korea. Human studies on mechanisms underlying HDLI have yet to be conducted. This study aimed to investigate methylation changes and their potential role in HDLI after exposure to HDs containing polyhexamethylene guanidine-phosphate. DNA methylation analysis was performed in blood samples from 10 children with HDLI and 10 healthy children using Infinium Human MethylationEPIC BeadChip. Transcriptome analysis was performed using lung tissues from 5 children with HDLI and 5 controls. Compared to healthy controls, 92 hypo-methylated and 79 hyper-methylated CpG sites were identified in children with HDLI at the statistical significance level of |Δβ|>0.2 and p<0.05. NOTCH1 was identified as a candidate network hub gene in cases. NOTCH1 transcripts significantly increased in lung tissues from HDLI cases compared to unexposed controls (p=0.05). NOTCH1 may play an important role in pulmonary fibrosis of HDLI.